ANALISIS KANDUNGAN LOGAM BERAT TIMBAL (Pb) DAN KADMIUM (Cd) PADA PERAIRAN SUNGAI SAIL KOTA PEKANBARU BERDASARKAN BIOINDIKATOR KEONG MAS (Pomacea canaliculata) SEBAGAI RANCANGAN MODUL BIOLOGI KONSEP PENCEMARAN LINGKUNGAN DI SMA - Sagita, Romi; ', Suwondo; ', Yustina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research was conducted to determine the content of heavy metals Lead (Pb) and Cadmium (Cd) on Water River Sail Pekanbaru based bioindikator snails (Pomacea canaliculata) as module design concept of environmental pollution biology in high school performed in June 2014. Determination research station is purposive random sampling by considering the environmental conditions based on community activities around the river. The main parameters in this study include heavy metals Pb and Cd in river water, sediment and Pomacea canaliculata, and physico-chemical parameters as supporting parameters. Hasi study showed that the average content of heavy metals in river water Pb and Cd 0.26 ppm 0.16 ppm where the heavy metal content in the water has passed the threshold of 0,008 ppm and 0,001 ppm Pb untu to Cd. The average content of heavy metals in the sediment of 3.04 ppm Pb and Cd 0.08 ppm. While the average content of heavy metals Pb Pomacea canaliculata 0.73 ppm and 0.21 ppm Cd. Where the content of heavy metals contained in the sediments and Pomacea canaliculata has not crossed the threshold that has been set. Further results of the study of heavy metals Pb and Cd in river water, sediment and Anadara granosa that have been implemented will serve as a source in the preparation of the learning modules in high school.Keywords: Pomacea canaliculata, heavy metals Pb and Cd, water pollution, Biology Module